STRATEGY TO INCREASE THE PERFORMANCE OF PROCUREMENT AT PT PLN (PERSERO) UIP SUMBAGUT - Nina Verawaty; Yeni Absah; Meilita Tryana (CV. Radja Publika, 2024)
Effective procurement is critical to improving business operational efficiency, reducing costs, and ensuring that required goods and services are available at the right quality and on time. In the 2020–2023 period, PT PLN (Persero) UIP Sumbagut faced problems in achieving contracted work targets, with an average of only 50% of the procurement plan. To achieve this, research needs to be conducted to evaluate the various components that influence procurement performance and develop solutions for improvement. This research uses a qualitative descriptive approach through observation and distribution of questionnaires, as well as case analysis and literature approaches. The TOWS analysis method is used to evaluate the strengths, weaknesses, opportunities, and threats faced during the procurement process. The results of the internal factor evaluation (IFE) and external factor evaluation (EFE) matrices show that this strategy is in Quadrant III, or the stabilization stage. The focus of this strategy is to maximize strengths and opportunities while reducing weaknesses and threats. The resulting strategies are accelerating the readiness of tender documents, optimizing the use of digital procurement, standardizing and updating tender documents and creating work instructions, utilizing information technology, increasing risk mitigation, increasing synergy and collaboration with stakeholders, as well as increasing HR competency.